Association of polymorphisms of the ADIPOQ, ADIPOR1 and ADIPOR2 genes with type 2 diabetes mellitus - Dmitry Sergeevich Khodyrev; Aleksey Georgievna Nikitin; Aleksey Nikolaevich Brovkin; Elena Yur'evna Lavrikova; Nadezhda Olegovna Lebedeva; Olga Konstantinovna Vikulova; Minara Shamkhalovna Shamkhalova; Marina Vladimirovna Shestakova; Valery Vyacheslavovich Nosikov; Alexander Vyacheslavovich Averyanov (Сахарный диабет)
The study of hereditary predisposition to multifactorial diseases is essential for diagnosis and selection of the optimal treatment. The study of polymorphisms of candidate genes whose products are involved in the pathogenesis of multifactorial diseases is of great clinical importance. Aim. The aim of this study was to investigate the association of rs2241766 and rs1501299 polymorphisms in the ADIPOQ gene, rs2275737 and rs2275738 polymorphisms in the ADIPOR1 gene and rs11061971 and rs16928751 polymorphisms in the ADIPOR2 gene with the development of type 2 diabetes mellitus (T2DM) in the Russian population. Materials and methods. The study included a group of 500 patients with T2DM diagnosed based on standard diagnostic criteria (T2DM+). The control group (T2DM-) was a random sample of 500 patients with no evidence of the disease and was matched to the T2DM+ group for gender, age and body mass index. The determination of alleles and genotypes was performed using real-time polymerase chain reaction with TaqMan probes. The X2 test and contingency tables were used to compare the distribution of allele and genotype frequencies. A p-value of